Konstruksi Gaya Hidup Gen Z Dalam Sinetron Asmara Gen Z: Analisis Resepsi Publik Di Media Sosial X Dan Tiktok - Muhammad Dzaudan Dzaki; Lisa Ahriyanti; Yunita Khorimah; Ayu Sri Wulandari; Aldi Fathi; Rafa Elpaz; Muhammad Ihsan; Aulia Kamalia; Novaria Maulina; Yuanita Setyastuti (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2026)
This study analyzes the digital public reception of the Gen Z lifestyle portrayed in the soap opera Asmara Gen Z using Stuart Hall’s (1980) encoding-decoding model and compares it with the sociological reality of Gen Z. A qualitative approach with qualitative content analysis was applied to identify and categorize public comments based on the AIO (Activities, Interests, Opinions) concept by Wells & Tigert (1983). Primary data was collected through Brand24 big data monitoring as well as manual observation on X and TikTok. Secondary data in the form of soap opera scene documentation was analyzed as a comparison for the encoding process. The results show that Gen Z’s lifestyle construction in soap operas is represented through social activities, interests in trends and self-image, as well as opinions regarding mental health and social relationships. Public reception is divided into three positions, including dominant, negotiation, and opposition. Some viewers consider these representations relevant to Gen Z’s lives, particularly regarding productive activities, appearance, and social issues like mental health. However, others felt that romantic conflicts were overly dramatized. These findings demonstrate that Gen Z audiences actively interpret media messages based on their personal experiences. The soap opera’s portrayal is close enough to reality to feel relatable, yet sufficiently dramatized to meet the entertainment industry’s needs. This study is expected to contribute to the field of communication, particularly in the study of audience reception.